Influence of Canning and Storage on Physicochemical Properties, Antioxidant Properties, and Bioactive Compounds of Apricot (Prunus armeniaca L.) Wholes, Halves, and Pulp - Jan, Nusrat; Anjum, Sadaf; Wani, Sajad Mohd; Mir, Sajad Ahmad; Malik, A. R.; Wani, Sajad Ahmad; Hussein, Dina S.; Rasheed, Rabab Ahmed; Gatasheh, Mansour K. (Frontiers in Nutrition, 2022)
The present research aimed to examine the effect of canning and storage on physicochemical, mineral, antioxidant properties, and phenolic composition of apricot wholes, halves, and pulp. The findings for physicochemical properties revealed that the TSS, titratable acidity, total sugars, and ascorbic acid, were found higher in apricot pulp (37.15%, 1.39%, 20.74%, 7.21 mg/100 g FW), respectively followed by apricot wholes and halves throughout the storage period. The remarkable contents of potassium, phosphorous, zinc, copper, iron, and manganese were found in the apricot pulp which revealed that canning and storage slightly affected the mineral composition. Bioactive substances were identified and quantified by RP-HPLC which indicated a higher presence of chlorogenic acid (34.45 mg/kg FW), quercitin-3-glucoside (16.78 mg/kg FW), neochlorogenic acid (26.52 mg/kg FW), gallic acid (5.37 mg/kg FW), kaempferol (14.22 mg/kg FW), ellagic acid (6.02 mg/kg FW), procyanidin B2 (8.80 mg/kg FW), and epicatechin (9.87 mg/kg FW) in apricot pulp followed by apricot wholes and halves throughout the storage period. TPC was found highest in apricot pulp (13.76 GAE mg/100 g FW) followed by wholes (8.09 GAE mg/100 g FW) and halves (6.48 GAE mg/100 g FW) which decreased significantly throughout the storage period. Antioxidant properties were assessed by DPPH, ABTS+, MCA, and BCBA which was found higher in the apricot pulp (92.23 TEAC µg g-1 DW, 92.33 TEAC µg g-1 DW, 33.80 TEAC µg g-1 DW, 68.40 TEAC µg g-1 DW), respectively that is correlated to the higher presence of bioactive compounds. Thus, apricot pulp containing excellent sources of nutrients, minerals, phytochemicals, and antioxidant components could be used as consuming purposes for providing nutraceuticals and antioxidants around the world.